2017
DOI: 10.1038/s41598-017-06417-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and tempo-flexible synchronization to a visual metronome in monkeys

Abstract: Predictive and tempo-flexible synchronization to an auditory beat is a fundamental component of human music. To date, only certain vocal learning species show this behaviour spontaneously. Prior research training macaques (vocal non-learners) to tap to an auditory or visual metronome found their movements to be largely reactive, not predictive. Does this reflect the lack of capacity for predictive synchronization in monkeys, or lack of motivation to exhibit this behaviour? To discriminate these possibilities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 48 publications
9
67
0
Order By: Relevance
“…We found that a rhesus monkey can transfer entrainment in the STF to a novel tempo (in this case 700 ms) without additional training. This is similar to the findings of Takeya et al ., who found that monkeys could generalize the predictive synchronization of eye movements with metronomic visual stimuli to untrained tempi. However, they tested three untrained IOIs, whereas we used only one.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We found that a rhesus monkey can transfer entrainment in the STF to a novel tempo (in this case 700 ms) without additional training. This is similar to the findings of Takeya et al ., who found that monkeys could generalize the predictive synchronization of eye movements with metronomic visual stimuli to untrained tempi. However, they tested three untrained IOIs, whereas we used only one.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the SCT dwell variability increased as a function of the interval following the scalar property of explicit timing observed in many tasks . However, the fact that the macaques’ asynchronies were lagging by 300 ms was interpreted as a sign that monkeys could not predict and instead were reacting to the metronome . The present STF results suggest that monkeys possess strong tapping predictive abilities and can produce NAs when the proper training and task conditions are provided.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations